Male infertility: An audit of 70 cases in a single centre - E.A. Jeje; T.O. Alabi; R.W. Ojewola; M.A. Ogunjimi; S.A. Osunkoya (African Journal of Urology, 2016)
Objectives: To audit the aetiology, treatment and predictors of outcome in infertile men who attended urology clinic of a private hospital in Lagos, Nigeria. Patients and Methods: A ten-year retrospective review of all male infertility cases managed in our facility. Data on the demography, presentations, clinical findings, aetiologies, investigations, treatments and outcomes of all patients seen over the study period were retrieved and analyzed. Results: A total of 70 married men were managed for male factor infertility with mean age of 35.6 years. Forty-four (62.9%) had primary while 26 (37.1%) had secondary infertility. The commonest aetiology of male infertility was varicocoele in 53 (75.7%) followed by testicular atrophy in 9 (12.9%) patients. Varicocoelectomy was done in 52 (74.3%), vaso-vasostomy in 3 (4.3%) and medical therapy in 15 (21.4%) of the patients. There was significant difference between the mean pre- and post-treatment sperm concentration and motility. Following treatment, sixteen (22.9%) and 31 (44.3%) patients had improvement in their sperm concentration and motility respectively out of which 13 (18.6%) achieved pregnancy. The mean post-treatment sperm concentration and motility in those who achieved pregnancy were 35.7 millions/ml and 68.5%, respectively. In those who had varicocoelectomy, the sperm concentration and motility were increased in 34 (77.3%) and 23 (53.5%), reduced in 4 (9.1%) and 11 (25.6%) and unchanged in 6 (13.6%) and 9 (20.9%), respectively. All the patients who achieved pregnancy were those who had varicocoelectomy representing 25% of those patients who had varicocoelectomy. Conclusion: Varicocoele represents the most common treatable cause of male factor infertility and treatment is accompanied with improved seminal fluid parameters as well pregnancy rate. Post-treatment sperm concentration and motility were the only factors that could predict the possibility of achieving pregnancy.